Dual-cell culture system with identical culture environment for comparison of anti-cancer drug toxicity. (18th May 2022) - Lai, Wei-Han; Mu, Hsuan‐Yu; Lu, Yu‐Lun; Chen, Hsin; Wen, Jyun-Wei; Wu, Hung-Jen; Cheng, Chao-Min; Huang, Jen‐Huang
Highlights: An all-in-one culture system can support two independent cell culture chips for drug toxicity study. The plug-and-play culture strategy helps the users to initiate the experiment conveniently and simply. The multilayered fabrication technology facilitates the integration of complex microfluidic structures in a single platform. The single pumping source generates two identical and dynamical culture conditions for the growth of the cells. The combination drug treatment in the dual-CS shows a synergistic effect for the cancer cells. Abstract: Tumor-on-a-chip technology that enables the dynamic culture of cell lines or clinical specimens on a microfluidic device offers new opportunities for clinical diagnosis, drug development, and toxicology test. Circulation is one of the key conditions to simulate tumor and other human-specific physiological environments. The peristaltic pump is an excellent tool to achieve the circulation culture condition. However, the complexity of the experimental setup, the cost of equipment, and experimental variations between culture units limit its widespread applications. Herein, we report a microfluidic-based dual culture system (dual-CS) that could simultaneously support two identical culture units for two independent drug tests using a single peristaltic pump. After continuously perfusing for 5 days, the difference in the flow rates between the two units remained<1%. To demonstrate the application, the dual-CS was used to investigate the toxicities of anti-cancer drugs toward A549 lung cancer epithelial cells. The cisplatin shows a dose-dependent effect on A549 cells, while pembrolizumab is non-toxic to the cells. The combination of cisplatin and pembrolizumab shows a synergistic effect on A549 cells. The dual-CS that simultaneously recapitulates an identical physiological environment for two culture units not only minimize the equipment cost but also reduces experimental variations between culture units.